(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Today, sport has taken a place in the life of society that has no analogies in history. His problems have become the subject of close study by physicians and educators, philosophers and historians, economists and sociologists. His influence is taken into account by politicians. The impact of sports on people’s moods and lifestyle is increasing. In this article, we can discuss information about some benefits of doing sport and physical activities in education system.